Supporting Akreditasi LAM Teknik: Evaluasi Implementasi MBKM di Fakultas Saintek UIN Sunan Kalijaga Yogyakarta - Awaliyah, Dien Fitri; Wardati, Khurul; Fatimah, Siti; Futhona, Aulia Khifah; Chasanah, Sri Istiyarti Uswatun (Universitas PGRI Semarang, 2023)
The fulfillment of the students’ rights to study for three semesters outside study programs is one program of Merdeka Belajar-Kampus Merdeka (MBKM) or Freedom to Learn-Independent Campus policy. The MBKM program has begun to be implemented at the Faculty of Science and Technology (Saintek) UIN Sunan Kalijaga Yogyakarta for almost 4 semesters. An evaluation has been conducted using the CIPP (Context, Input, Process and Product) evaluation model to assess its effectiveness. The results of the evaluation indicate that the program has had a positive impact on student achievement, although it has not yet met the standard for LAM Engineering accreditation that is having a certain number of outbound participants with a minimum of 20 credits. However, the program is trending in a positive direction, and it is hoped that it will continue to improve and provide benefits for all stakeholders particularly in support of LAM Engineering accreditation assessments.